Policy Role in Innovation Network: Case of Indonesian food processing firms - Erman Aminullah; Wati Hermawati; Trina Fizzanty; Nur Laili (STI Policy and Management Journal, 2020)
The objective of the study is to reveal factors that are internal and external to firms that affect the use of network relations for innovation, with a focus on mapping the policy role in innovation networks. The study was undertaken through case analysis in four different firms. The study found that the number of actors in network relations affects upgrading of value of a good or service. The upgrading is activated by learning events, which are related to organizational changes, namely, refocusing on the core business, restructuring the internal organization, undertaking management change, and applying responsive management practices. The specific policy role in stimulating the network effect for innovation are: (i) government facilities for the ease of doing business by continuing to reduce bureaucratic processes to regulate standard requirements, (ii) strengthening government agencies–industry relations by establishing promotion of representatives of Indonesian food products overseas, (iii) government brokerage and matching services for global trading by arranging trade fairs, business seminars, or supporting modern information technologies, and (iv) government relaxation on import restriction to maintain a stable supply of raw materials for food processing. The substantive contribution of this scientific study is the provision of the concept of policy role in innovation networks viewed from the sectoral system of innovation. Keywords: innovation network, policy role, organizational change, upgrading, sectoral system of innovation